2009
DOI: 10.4049/jimmunol.0801711
|View full text |Cite
|
Sign up to set email alerts
|

NAD+ and ATP Released from Injured Cells Induce P2X7-Dependent Shedding of CD62L and Externalization of Phosphatidylserine by Murine T Cells

Abstract: Extracellular NAD+ and ATP trigger the shedding of CD62L and the externalization of phosphatidylserine on murine T cells. These events depend on the P2X7 ion channel. Although ATP acts as a soluble ligand to activate P2X7, gating of P2X7 by NAD+ requires ecto-ADP-ribosyltransferase ART2.2-catalyzed transfer of the ADP-ribose moiety from NAD+ onto Arg125 of P2X7. Steady-state concentrations of NAD+ and ATP in extracellular compartments are highly regulated and usually are well below the threshold required for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
138
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 115 publications
(143 citation statements)
references
References 79 publications
3
138
1
1
Order By: Relevance
“…5). + T cells might be susceptible to extracellular ATP or NAD + generated during in vitro cell preparation (21). Upon adding 100 mM ATP for 15 min in a shortterm culture, we observed significantly greater downregulation of CD27 in the peritoneal CD49d (Fig.…”
Section: + T Cells In the Peritoneal Cavitymentioning
confidence: 52%
“…5). + T cells might be susceptible to extracellular ATP or NAD + generated during in vitro cell preparation (21). Upon adding 100 mM ATP for 15 min in a shortterm culture, we observed significantly greater downregulation of CD27 in the peritoneal CD49d (Fig.…”
Section: + T Cells In the Peritoneal Cavitymentioning
confidence: 52%
“…рис.4,а), але не в самих еритроцитах (див. рис.4,б) у старих щурів за дії урфугему, внаслідок можливого звільнен-ня при їх гемолізі АТФ, який діє на ці фер-менти синтезу NO через свої пуринорецеп-тори на плазматичних мембранах лейкоцитів [17]. У разі дії препарату більш ніж у 3 рази підвищувався індекс спряження сNOS в плаз-мі крові старих тварин (див.…”
Section: показникunclassified
“…Previous studies have shown that gating of the P2X7 ion channel by extracellular ATP or by NAD + -dependent ADP-ribosylation induces ectodomain shedding of CD62L (4,5). To assess whether the observed downmodulation of ARTC2.2 is also mediated by ARTC2.2-catalyzed ADP-ribosylation of P2X7, we tested whether available Abs against ARTC2.2 or P2X7 could block this phenomenon (Fig.…”
Section: Nad + -Induced Downmodulation Of Artc22 Is Mediated By Adp-mentioning
confidence: 99%
“…These nucleotides are released from cells during inflammation and tissue damage and modulate T cell functions (10)(11)(12)(13)(14). Gating of P2X7 induces externalization of phosphatidylserine, shedding of metalloprotease-sensitive membrane proteins, blebbing, and pore formation (5,(15)(16)(17)(18). P2X7 is gated either directly by high concentrations of ATP acting as a soluble ligand, or indirectly by NAD + -dependent ADP-ribosylation, a covalent modification catalyzed by ecto-ADP-ribosyltransferase ARTC2.2 (5,19).…”
mentioning
confidence: 99%
See 1 more Smart Citation